If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7x + 2 = 5x + 3 Reorder the terms: 2 + 7x = 5x + 3 Reorder the terms: 2 + 7x = 3 + 5x Solving 2 + 7x = 3 + 5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5x' to each side of the equation. 2 + 7x + -5x = 3 + 5x + -5x Combine like terms: 7x + -5x = 2x 2 + 2x = 3 + 5x + -5x Combine like terms: 5x + -5x = 0 2 + 2x = 3 + 0 2 + 2x = 3 Add '-2' to each side of the equation. 2 + -2 + 2x = 3 + -2 Combine like terms: 2 + -2 = 0 0 + 2x = 3 + -2 2x = 3 + -2 Combine like terms: 3 + -2 = 1 2x = 1 Divide each side by '2'. x = 0.5 Simplifying x = 0.5
| 6(79-5x)=11(4x-4) | | 180-x=.4(x)+5 | | 2(x+3)=8x-33 | | Y=10x^3+6 | | 13x-8y=-711 | | 8+2=-5(4x+2) | | 4(3x+9)=-32+44 | | 4(5x-2)=18 | | 2y=-8xy | | 13x-936=12x-624 | | 8xy=-2y | | y^2+3y=40 | | 0=(18(x^2))/((1-2(x^3))^2) | | x=155y+20 | | 7(9x+2)=5(16x-4) | | 2.8x=10.64 | | c=-(-12) | | z=-(18) | | g+-10=1 | | 7(9x+2)=11(16x-4) | | 0.09xX=70.17 | | 6x-2y+7=0 | | 7(9x+2)=4(4x-1) | | -3a^2-4a(2a+3)+7(a-8)= | | y=-.5x^2+0.7x-5.1 | | 6z+6z-10z=20 | | 0=3x-4/5 | | 0=3x-5/5 | | 5x-x-4=16 | | 11a-a-9a+3=17 | | 18d-12d-5=19 | | 6u+5u-8u-3=18 |